The Influence Of Head Nurses’ Leadership Styles On Staff Nurses’ Performance In Delivering Nursing Care At The Inpatient Wards Of Rsi Malahayati Medan - Fauziah Saragih; Thomson P Nadapdap; Ismail Efendy (Journal of Innovative and Creativity, 2025)
Nurse performance is a series of activities of nurses in providing an action or nursing care to patients. Good performance is a reflection of the quality of nursing services provided by nurses. Data on the quality of nursing at RSI Malahayati Medan in 2024 is 75.8% of the performance of executive nurses in the good category, 15.9% of the performance of executive nurses in the sufficient category and 8.3% of the performance of executive nurses in the less assessment category including documentation of nursing care. The purpose of the study was to analyze the effect of the leadership style of the head of the room on the performance of the executive nurse in the implementation of nursing care in the inpatient room of RSI Malahayati Medan. The research design used Analytical Survey method with Cross Sectional approach. The population in this study were all executive nurses who served in the inpatient room as many as 70 people, all of whom were used as research samples with total population techniques. Data analysis used univariate analysis, bivariate with chi-square test and multivariate with logistic regression. The results of logistic regression research indicate that there is a democratic influence p = 0.003, laisses faire (free to act) p = 0.003, participatory p = 0.005 and transpormative p = 0.013. While the dominant factor influencing the performance of executive nurses is democratic p = 0.001 with Exp (B) 85.754, meaning that democracy has 85 times the risk compared to other variables. The conclusion of this study is that there is a democratic, free-action, participatory and transformative influence on the performance of implementing nurses in the implementation of nursing care in the inpatient room of RSI Malahayati Medan and variables that have no effect are authoritarian. It is recommended that the head of the room in carrying out the leadership function should be democratic, namely making decisions based on deliberations with other teams that are adjusted to the situation so that it will produce effective leadership so as to make subordinate performance better and of higher quality.